IMPLEMENTATION AND EVALUATION OF HEALTH SCREENING SERVICES TO DIABETIC AND HYPERTENSIVE PATIENTS IN A SELECTED COMMUNITY PHARMACY AT BELGAUM CITY - Sushilkumar PL; MAHENDRAKUMAR BJ; SUMAN BAISHNAB; GLORIA SAM K; CHAITANYA KUMAR T (Asian Journal of Pharmaceutical and Clinical Research, 2015)
OBJECTIVE: To select, set up and initiate the health screening services in the community pharmacy, to design and develop patient data collection form and patient identity card, to implement health screening services in a selected community pharmacy & to evaluate the health screening services data. METHOD: The study was a prospective, investigational and community interventional study, conducted for a period of ten months from May 2008 to February 2009. RESULT: 98 patients and 24 customers under risk factors were screened during the study. Out of which 58 (59.18%) patients were diabetic with hypertensive, 26 (26.53%) were hypertensive and 14 (14.28%) were diabetic. The systolic and diastolic blood pressure, random blood sugar and body mass index values of the screened patients reveals the need for the provision of health screening services in the community pharmacy by a pharmacist. Various demographic factors like age, gender, occupation, economic status, educational background, periodic check-up showed equal impact of pharmacist involvement and need to provide these services in the community pharmacy. CONCLUSION: This study suggest that there is ample scientific evidence showing that certain risk factors pre-dispose individuals to development of diabetes and hypertension, there is sufficient evidence to conclude that community screening is a cost effective approach to reduce the morbidity and mortality associated with these diseases in healthy individuals. Community screening programs may provide a means to enhance public awareness regarding seriousness of diabetes and hypertension and its complications. Â KEYWORDS: Health Screening Services, Community Pharmacy, Diabetes, Hypertension.